Kajian terhadap Pemeriksaan Haemoglobin (Hb) - Ratna Indriawati (Universitas Muhammadiyah Yogyakarta, 2002)
The prevalence of anemia among pregnant women and under-five-year- old children in Indonesia is still very high. Hemoglobin (Hb) estimation assists in detecting anemia. There are two methods on measuring Hb by colorimetries i.e. Sahli and Talquist. The objective of this study was to compare the value of Sahli and Talquist methods by using the agreement test. This study was conducted in Physiology Laboratory, Faculty of Medicine, Muhammadiyah University of Yogyakarta. A total number of 39 students who took Physiology were enrolled to this study. The Hb level measurement was conducted by trained students. Two students conducted the Hb level measure-ment using Sahli and Talquist methods randomly. Subjects of the study were 39 students consisted of 18 men and 21 women. The age mean was 20 ± 2,2. Using Talquist method, the Hb levels among men were significantly higher than women (p-0.02). Kappa coeffisient was calcu-lated to know the agreement between Sahli and Talquist methods. The Hb levels were catagorized into two groups using cut-off point 12 mg/dl, 10 mg/dl and 8 mg/dl, respectively. The agreement based on those three cut-off point was low, kappa coefficient were 0.24, 0.20 and 0.22, respectively. There were differences on the Hb level measurement between Sahli and Talquist methods (the agreement test with K=0,24; K=0,22 and K=0,20 were low).Prevalensi anemia pada wanita hamil dan anak-anak di bawah lima tahun di Indonesia masih sangat tinggi. Untuk menentukan adanya anemia perlu pemeriksaan kadar hemoglobin (Hb). Pemeriksaan kadar Hb secara kolorimetris ada 2 cara yaitu, metode Sahli dan Talquist Tujuan dari penelitian ini adalah membandingkan hasil pengukuran kadar Hb menggunakan metode Sahli dan Talquist dengan uji kesepakatan. Penelitian ini dilakukan di Laboratorium Fisiologi, Fakultas Kedokteran Univer-sitas Muhammadiyah Yogyakarta. Jumlah subyek 39 orang mahasiswa yang mengambil matakuliah fisiologi. Mahasiswa sebelumnya dilatih dahulu. Dua orang mahasiswa melakukan pemeriksaan Hb dengan metode Sahli dan Talquist, secara acak. Subyek penelitian ini adalah 39 mahasiswa, terdiri dari 18 laki-laki dan 21 perempuan, yang berusia rata-rata 20 +2,2 tahun. Pemeriksaan kadar Hb metode Talquist didapatkan perbedaan bermakna antara kadar Hb laki-laki dan perempuan (p=0,02). Perhitungan dengan koefisien Kappa untuk mengetahui kesepakatan antara metode Sahli dengan Talquist. Kadar Hb dikategorikan diam 2 kelompok menggunakan cut-off point 12 g/dl, 10 g/dl dan 8 g/dl. Uji kesepakatan pada 3 cut¬off point tersebut rendah, koefisien Kappa 0,24,0,20 dan 0,22. Terdapat perbedaan hasil pemeriksaan kadar Hb metode Sahli dan Talquist (uji kesepakatan dengan K=0,24, K=0,22 dan K=0,20 rendah).